EMU Detection of a Large and Low Surface Brightness Galactic SNR G288.8-6.3 - Filipović, Miroslav D.; Dai, Shi; Arbutina, Bojan; Hurley-Walker, Natasha; Brose, Robert; Becker, Werner; Sano, Hidetoshi; Urošević, Dejan; Jarrett, T. H.; Hopkins, Andrew M.; Alsaberi, Rami Z.E.; Alsulami, R.; et al. (Astronomical Journal, 2023)
We present the serendipitous detection of a new Galactic supernova remnant (SNR), G288.8-6.3, using data from the Australian Square Kilometre Array Pathfinder (ASKAP) Evolutionary Map of the Universe (EMU) survey. Using multifrequency analysis, we confirm this object as an evolved Galactic SNR at high Galactic latitude with low radio surface brightness and typical SNR spectral index of α = − 0.41 ± 0.12. To determine the magnetic field strength in SNR G288.8-6.3, we present the first derivation of the equipartition formulae for SNRs with spectral indices α > − 0.5. The angular size is 1.°8 × 1.°6 (107.′6 × 98.′4), and we estimate that its intrinsic size is ∼40 pc, which implies a distance of ∼1.3 kpc and a position of ∼140 pc above the Galactic plane. This is one of the largest in angular size and closest Galactic SNRs. Given its low radio surface brightness, we suggest that it is about 13,000 yr old.
CRIS-Team Scopus Importer:2023-09-22